Three Milestones of Latvian Translation Criticism - Veisbergs, Andrejs; Ločmele, Gunta (Vertimo studijos, 2023)
The article provides insight into the development of translation criticism from 1920s to 1980s in Latvia by offering translations of excerpts from theoretical texts that map important events in translation history. We start with the book, published in 1924, which evaluated the 1689 translation of the Bible into Latvian, then concentrate on a polemical article by Rainis (1925) on his innovative 1897 rendition of Goethe’s Faust and finish the analysis with a discussion of a work written in 1984. The latter stood out during the Soviet era by drawing attention to the aesthetic values of translation, contrasting with the prevailing focus on linguistic aspects, specifically the quality of the Latvian language. Each of these three works, in its own manner, exerted influence both on the historico-philosophical ideas of its era and on the evolution of translation in Latvia. The review and translations of these three excerpts are contextualized through an analysis of Latvian translation history. It is stressed that despite censorship, the Soviet-time translations spread the ideas that often contradicted the Soviet ideology as well as opened new broader vistas for language use.